Determinanty korzystania ze strategii uczenia się języka angielskiego przez studentów poznańskich uczelni - Przybył, Jakub (Neofilolog, 2017)
The study described in the present paper aimed to account for all the three dimensions of learners’ strategic self-regulation, i.e. cognitive, affective, and sociocultural-interactive language learning strategies (LLS) (Oxford 2011), and attempted to explore their relationships with learners’ personality and other individual variables, such as gender, type of university and area of studies, or the level of proficiency in English. The participants of the study, who formed a representative sample of BA/BS students of AMU and WSB University (722 students in total), completed two questionnaires, a Polish adaptation of SILL ver. 7.0 (Oxford 1990), and the adaptation of NEO-FFI recommended by the Polish Association of Psychology (Zawadzki et al. 2010) for research. The goodness criteria for psychometric research tools (Hornowska 2007) were analysed for both questionnaires. The obtained results confirm the role of most of the above-mentioned individual characteristics in strategy choice, validate the importance of learners’ personality in language learning, and provide evidence of the significance of openness to experience in learning a foreign language.